Prevalence of temporomandibular joint disorders in outpatients at Al-Badar Dental College and Hospital and its relationship to age, gender, occlusion and psychological factors - Raheel Ahmed Syed; Arshiya Ara Syeda; Girish Katt; Vini Arora (Wolters Kluwer Medknow Publications, 2012)
Background: Temporomandibular disorder (TMD) is a collective term that encompasses many clinical problems involving the masticatory muscles, temporomandibular joints (TMJ) and associated structures and it has high prevalence among populations. Aims and objectives: To determine the prevalence of TMD and its relationship to age, gender, occlusion and psychological factors and to evaluate which age group, gender, malocclusion parameters and psychological factors contribute to the prevalence of TMD. Materials and methods: The study includes a sample of 250 young adults (134 girls and 116 boys) with age ranging from 18 to 25 years, the presence and severity of TMD was determined using a self-administered anamnestic questionnaire composed of 10 questions regarding common TMD symptoms. Morphologic occlusion was evaluated according to Angle's classification (molar classes I, II, III) and to evaluate the psychological factors, The hospital anxiety and depression scale (HADS) developed by Zigmond and Snaith was used. Results: Data were computerized and the SPSS package (version 11.2) was used and nonparametric test of Chi-square for data analysis and unpaired t-test was also used for statistical data analysis. Anamnestic index (AI) showed that the percentage of women (5522%) had higher degree of TMD symptoms than compared with men (50.86%), comparing the age of men and women free TMD and with TMD, the statistical difference was not significant as (t = 1.35, p > 0.5), distribution of the cases among Angle's class I, II, III occlusion the difference was not statistically significant as (p > 0.5), the degree of anxiety and TMD degree among men and women patients, women had higher anxiety levels as compared to men and no statistical difference was found between the cases of men and women in the depression levels. Conclusion: Prevalence of TMD symptoms in our sample of 250 patients was high for women- Morphologic occlusion was not associated with the presence of TMD symptoms. By considering the psychological factors we found anxiety but not depression associated with TMD symptoms.